2016
DOI: 10.1109/tiv.2016.2555626
|View full text |Cite
|
Sign up to set email alerts
|

Humans and Intelligent Vehicles: The Hope, the Help, and the Harm

Abstract: Abstract-Intelligent vehicles offer hope for a world in which crashes are rare, congestion is reduced, carbon emissions are decreased, and mobility is extended to a wider population. As long as humans are in the loop, over a half century of research in human factors suggests that this hope is unlikely to become a reality unless careful attention is paid to human behavior and, conversely, the potential for harm is real if little attention is given to said behavior. Different challenges lie with each of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…We have submitted our results to the Kaggle and appeared on the top 17% in the leaderboard. The winner 1 used empirical tricks such as focusing head and driver's right hand 1 https://www.kaggle.com/c/state-farm-distracted-driver-detection/ discussion/22906 regions for fine-grained representations resulting in higher recognition accuracy. We would like to emphasise that our approach using the proposed high-level feature is simple yet effective and semantically rich.…”
Section: A Performance On State Farm (Sf) Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…We have submitted our results to the Kaggle and appeared on the top 17% in the leaderboard. The winner 1 used empirical tricks such as focusing head and driver's right hand 1 https://www.kaggle.com/c/state-farm-distracted-driver-detection/ discussion/22906 regions for fine-grained representations resulting in higher recognition accuracy. We would like to emphasise that our approach using the proposed high-level feature is simple yet effective and semantically rich.…”
Section: A Performance On State Farm (Sf) Datasetmentioning
confidence: 99%
“…It offers our desire for a better world in which injuries and fatalities from accidents are rare, congestion is lesser, and many societal and environmental benefits are far greater. It is suggested that this desire is unlikely to become a reality unless mindful attention is paid to human behaviour [1] since human error is overwhelmingly to blame for the vast majority of automobile accidents [2]. Today's automobile is nearly autonomous due to Advanced Driver Assistance System (ADAS) and is feasible due to ultrasonic sensors, cameras, radars and lidars.…”
Section: Introductionmentioning
confidence: 99%
“…The NTSB recognises that decades of research has shown that humans are notoriously inefficient at monitoring automated systems (e.g. Casner & Schooler, 2015;Fisher et al 2016;Molloy & Parasuraman, 1996) and provide a number of recommendations in an effort to improve system transparency and safety. However, the report still fails to explain why the driver felt able to relinquish control in the way that they did.…”
Section: What We Think Happenedmentioning
confidence: 99%
“…Most of these sensing technologies are often focused on surrounding environmental perception and minimal work has focused on the human driver perspectives. It is suggested that mindful attention should be paid to driver behavior [11] since driver error is overwhelmingly to blame for the vast majority of accidents [35,1]. The driver's role could be replaced by the AVs but the vehicle also requires to deliver performance identical to that of a driver if it is to be trusted [21].…”
Section: Introductionmentioning
confidence: 99%